PENGARUH SUBSTITUSI PARSIAL SEMEN DENGAN ABU TERBANG TERHADAP KARAKTERISTIK TEKNIS BETON - Simatupang, Partogi H.; Sir, Tri M. W.; Kurniaty, Anna S. (Jurnal Teknik Sipil, 2016)
Partly or totally substitution of cement with another environmentally products in making concrete become the alternative. In this research the composition of the fly ash used as a partial replacement of cement in concrete as much as 40% out of total mass of cement (High Volume Fly Ash Concrete) and then will be compared with normal concrete about the technical characteristics of the two types of concrete. The purpose of this research was to determine the effect of partial replacement of cement with fly ash in concrete on technical characteristics of concrete which are specific gravity of concrete, compressive strength of concrete and concrete abrasion. The results obtained by the technical characteristics of concrete at the concrete age of 56 days for normal concrete has an average of specific gravity is 2434.39 kg/m³ with an average of compressive strength is 22.72 MPa and concrete abrasion percentage is 19.74%, for HVFA concrete has an average of specific gravity is 2407.22 kg/m³ with an average of compressive strength of 22.51 MPa and concrete abrasion percentage is 20.12%. The result of this research shows that the effect of the partial replacement of cement with fly ash in concrete produce the technical characteristics of concrete which are specific gravity of concrete, compressive strength of concrete and concrete abrasion are similliar with the technical characteristics of normal concrete.